Transformasi Paradigma Teologi Teosentris Menuju Antroposentris:Telaah atas Pemikiran Hasan Hanafi - M. Gufron (Millati: Journal of Islamic Studies and Humanities, 2018)
Hassan Hanafi is one of the contemporary Islamic scholars who gives considerable attention to classical Islamic theology (kalam Islam). For him Islamic theology, such as the Ash’ari’s Kalam, cannot be proven scientifically also philosophically. Classical Islamic theology practically cannot be used as a view that can motivate the increasing of concrete actions in human life. This is caused by the compilation of classical Islamic theology tends not to be based on the pure awareness and the values of human actions. So that this creates a split between the theoretical faith into the practical faith of ummah. In turn, this conditions create the multiple moral attitudes or secretism of personality that makes Islamic society worse in poverty, oppression, backwardness and ignorance. For this problems, Hassan Hanafi offered a reconstruction that is to change a more grounded theological paradigm; that is from theocentric (God is the central of everything) to be anthropocentric (humanbeing is the central of everything). If the first paradigm sees world affairs as a matter of God, then the second paradigm sees world affairs as human affairs.